Correlation Between Automated And The Westergren Method For Determination - Hina Mushtaq; Tariq Mehmood; Imran Khan; Nabila Razvi (Journal of Bahria University Medical and Dental College)
Objective: To determine the correlation between automated and the Westergren method for determination of ESR in symptomatic patients. Study Design and Setting: This cross sectional study conducted at Hematology Department of PNS Shifa Hospital Karachi. Methodology: Sample size was determined by using WHO sample size calculator. Westergren method was performed according to ICSH’s specifications. ESR vacuum tubes containing sodium citrate were used. The sedimentation of the RBC’s was recorded visually after 1 hour using a timer. Automated ESR was performed by TEST1 automated ESR analyzer (ALIFAX SpA, Italy). It uses K3-EDTA or K2-EDTA as an anticoagulant. Bias was controlled by inclusion and exclusion criteria and the confounding factors like temperature of lab and effect of wind were controlled by taking appropriate measures. Pre-designed proforma was used to collect the data that was analyzed through SPSS version 16. Correlation between the two methods was measure through Pearson correlation coefficient analysis. Results:. The ESR measured by Westergren method ranged from 2 mm/1st hour. to 131 mm/1st hour, with a mean of 39.94±29.60 mm/1st hour. while ESR measured by automated method ranged from 2 mm/1st hour. to 120 mm/1st hr. with a mean of 41.67±32.43 mm/1st hour. There was significantly strong correlation between automated and the Westergren method for determination of ESR (r =0.945; p = <0.001). Similar results were observed across all ages, gender, duration and type of symptoms groups. Conclusion: Automated and the Westergren method are strongly correlated. Automated method can be used in place of Westergren method for determination of ESR.